Facile Synthesis of Nanostructured Lithium-Incorporated Titanium Oxides (Li-TiOx) by Means of Wet Corrosion Process (WCP) and Their Potential Application for Batteries - Suzuki, Hiroto; Nishiguchi, Takumi; Igawa, Yuta; Oshiumi, Hiroya; Lee, Ki-Young; Kim, Sanghoon; Im, Eunji; Lee, Siha; Kim, Haneul; Yoshikubo, Hatsuko; Kiyono, Hazime; Lee, So Yoon (ACS Publications, 2025)
Currently, there is a growing demand for nanomaterials in the fields of materials and energy. Nanostructured metal oxides have been widely studied, owing to their unique and diverse physicochemical properties and potential applications in various fields. In recent years, considerable attention has been directed toward metal oxides, particularly lithium-incorporated titanium oxides (Li-TiOx), owing to their exceptional safety profiles. This material has been used in automotive battery systems, which has prompted extensive research efforts to enhance its functional properties. In response to the demand for superior nanomaterials, this study attempts to fabricate nanostructured Li-TiOx using a wet corrosion process (WCP). WCP refers to a novel method for fabricating nanostructures that employ alkaline solutions. This technique offers numerous advantages, such as short processing times, high reproducibility, and low cost. As a result of experiments, nanostructured Li-TiOx were successfully fabricated using LiOH solutions ranging in concentration from 0.5 to 2 mol/L. The fabricated nanostructures exhibited superior characteristic properties, such as increased surface area and enhanced electrical properties, when compared with those of untreated titanium. This study demonstrates that WCP is a simple, versatile, and scalable method for producing nanostructured Li-TiOx tailored for battery applications.